A global crisis manager during the COVID-19 pandemic? The OECD and health governance - Meier, Sooahn; Martens, Kerstin (Frontiers in Political Science, 2024)
The COVID-19 pandemic has triggered turbulent times across the globe, reminding us of the highly multidimensional and interdependent nature of today's world. Next to differing national attempts to constrain the spread of the virus, numerous international organizations worked intensely to minimize the impacts of the disease on a regional or/and global scale. Albeit not considered a conventional agency responsible for global infectious diseases, the Organisation for Economic Co-operation and Development (OECD) has surprisingly been one of the most proactive IOs in the pandemic response. In this context, this article examines to what extent the OECD's COVID-19 pandemic response adheres to the role of a global crisis manager. By adapting the theoretical concepts of crisis leadership, we explore the extent of sense-making, decision-making, and learning capacities of the OECD during the pandemic to examine the organization's position-making. Based on expert interviews and document analysis, this paper illustrates that the OECD perceived the pandemic as an exogenous shock that spilled over across broad socioeconomic sectors, severely affecting its member states. This sensemaking enabled prompt multilayered top-down as well as bottom-up decision-making to advise member states by providing policy options. However, the OECD's engagement during the crisis was proactive only to the extent that several limitations allowed, such as resource inflexibility and internal dynamics between the Secretariat and Member States. In conclusion, we argue that the OECD did not present itself to be a global crisis manager during the COVID-19 pandemic, but rather, its activities consolidated its position-making as a policy advisor for member states.